Development of Literacy in Islamic Education in the COVID-19 Pandemic Era for Elementary School - Febriani, Suci Ramadhanti; Safutri, Janniarni Toha; Yusnawati, Yusnawati; Anasrudin, Anasrudin (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2020)
The challenges of education during the Corona Virus DiseasesÂ (COVID-19) pandemic are increasingly complex. The internalization process of literacy activities needs to be improved in an effort to improve the quality of human resources in the global realm. This research aims to explore strategies in improving the literacy of students during COVID-19 and the problems faced by teachers during the literacy development process at Mutiara Hati Elementary School in Malang, Indonesia. This research uses a qualitative approach with case study methods. The data source was taken using observation, interview and documentation with data analysis techniques using triangulation techniques with three stages; collection, reduction, and conclusion. The results showed four strategies can be done to improve literacy activities that, strategies used can be done to improve the literacy culture of students through four ways; webinar activities, ongoing mentoring, work monitoring and distribution of students' literacy results. While in the problematic aspects faced by teachers there are three aspects, namely the limitations of competency in designing media, the limitations of discussion space on the work of students and the lack of supporting facilities to monitor the work of students. The findings of this study have manifestly shown that the integration of media, strategies and competencies of ideal teachers can provide positive output for creativity and critical thought processes of students in making work. This study recommends further research to test the effectiveness of literacy activities and the use of broader research methods of reach and problematic solving faced by teachers.